Schaum's Outline Series Theory and Problems of Engineering Mechanics : Statics and Dynamics - MCLEAN, W.G, NELSON, E.W (McGraw Hill, 1987)
Schaum's Outline Series Theory and Problems of Engineering Mechanics : Statics and Dynamics